Unified OPF method for maximizing voltage stability margin using successive fuzzy LP - Venkatesh, B.; Arunagiri, A.; Gooi, H. B. (Elsevier Science, 2003)
This paper proposes a new unified OPF method that optimally schedules real and reactive power controllers. It minimizes the total generation cost and system transmission loss while maximizing the system voltage stability margin (VSM). VSM is maximized by maximizing a set of few least singular values of the load flow Jacobian. The method employs a successive fuzzy LP technique. Fuzzy models of the violated operating constraints are used. The use of fuzzy models allows scheduling of stressed power systems having violated operating constraints and gets their best enforcement. Sparse matrix computing techniques and constant network matrices are employed to realize the practical applicability. The proposed method is tested on modified IEEE 6- and 30-bus systems and on a 191-bus Indian electric system. Results serve to demonstrate the practical utility of the method. (C) 2002 Elsevier Science B.V. All rights reserved.